2004
DOI: 10.1038/sj.jp.7211097
|View full text |Cite
|
Sign up to set email alerts
|

Actinomyces Species and Cerclage Placement in Neonatal Sepsis: A Case Report

Abstract: A 26-year-old female with a history of preterm labor and cerclage placement presented at 29 weeks gestation. Twin girls were delivered at 29 1 7 weeks. Twin A presented with clinical sepsis at birth. Twin A's blood cultures became positive for Actinomyces species on day of life 15. Despite aggressive medical management twin A died at 35 days of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Infections of the urogenital tract 19 , eye [20][21][22] , skin, and disseminated disease 23,24 focalized in the central nervous system (CNS) 25 are rare; a case of chronic lymphadenitis has also been reported 26 . Only vertical transmission has been reported, and two cases of neonatal sepsis have been described: one caused by A. neuii and the other (species unidentified) with uterine cerclage as the identifiable risk factor 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Infections of the urogenital tract 19 , eye [20][21][22] , skin, and disseminated disease 23,24 focalized in the central nervous system (CNS) 25 are rare; a case of chronic lymphadenitis has also been reported 26 . Only vertical transmission has been reported, and two cases of neonatal sepsis have been described: one caused by A. neuii and the other (species unidentified) with uterine cerclage as the identifiable risk factor 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…In our literature review, we identified 16 cases of Actinomyces in pregnancy (Table 1), [6][7][8][9][10][11][12][13][14][15][16][17][18][19] and we have had a single case at our hospital. We were unable to obtain 1 article from Croatia.…”
Section: Pathophysiology Of Actinomyces In Pregnancymentioning
confidence: 99%
“…14,19 It is uncertain whether the cerclage incited a response in which Actinomyces was able to invade the normal defenses of the membranes resulting in the chorioamnionitis. In 2 of these cases, the patient had a cerclage in place.…”
Section: Pathophysiology Of Actinomyces In Pregnancymentioning
confidence: 99%
See 2 more Smart Citations